Analisis Pola Asuh Orang Tua dalam Membentuk Karakter pada Anak Usia Dini - Novia, Bagas Oktaris Novia; Rachmawati, Yeni (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Parents have a significant role in shaping their children's character from an early age through proper parenting. The parenting style applied by each parent varies greatly, adjusted to the conditions of the parents and also the needs of the child and is influenced by many other factors. Therefore, the purpose of this study is to analyze the parenting patterns applied by parents in shaping certain characters in early childhood. This research uses the Systematic Literature Review (SLR) method. Data searches were conducted using the google scholar electronic database. Then analyzed descriptively by setting inclusion and exclusion criteria. Based on the results of the study, 3 forms of parenting were obtained, namely democratic, authoritarian, and permissive in shaping character in children. Parents can combine these forms of parenting according to the situation, conditions and the right portion. The character values that can be formed through the combination of parenting are tolerance, independence, polite, religious, respectful, disciplined, caring, adaptable, honest, responsible, confident, hard work, friendly, open attitude, simple, brave, fair, patient, and leadership. From the results of this study, it is hoped that parents can be wiser in applying parenting patterns for their children and not only focus on one parenting pattern that is considered the best.